EPIZOOTOLOGICAL MONITORING OF OPPORTUNISTIC MYCOSES IN THE TURKESTAN REGION AND IDENTIFICATION OF PATHOGENS - Kairatova Z. G. (Reviews of Modern Science, 2024)
In recent decades, the importance of fungal infections in both humans and animals has increased. Opportunistic mycoses are the cause of a wide range of diseases - from localized infections to deadly disseminated diseases such as aspergillosis, mucormycosis, candidiasis, cryptococcosis and infections caused by melanized fungi [1]. Fungi are particularly sensitive to the effects of climate change because the greatest diversity and biomass of fungi are found in the upper soil layer, which is at the forefront of environmental change. Fungal diseases cause a wide range of diseases, ranging from mild infections of the skin and mucous membranes to severe respiratory diseases and life-threatening disseminated diseases. According to D. Corrêa-Moreira, B. de Oliveira and others (2022), changes in weather conditions contributed to the expansion of the geography of endemic fungi, the emergence of new pathogens and increased resistance of pathogens to antifungal drugs [2].